Sie sind auf Seite 1von 10

# 1.

## (a) Since is a complex number which satisfies

3
1 = 0, 1. Hence,
1 + +
2
=

1
1
3
= 0. (M1)(A1)
2

(b) ( x +
2
y)(
2
x + y) =
3
x
2
+
4
yx +
2
xy +
3
y
2
. (M1)
Using
3
= 1 and
4
= , we get, (M1)
( x +
2
y)(
2
x + y) = (x
2
+ y
2
) + (
2
+ )xy (M1)
= x
2
+ y
2
xy, (Since l + +
2
= 0) (A1)
4
[6]

2. (a) z
5
1 = (z 1)(z
4
+ z
3
+ z
2
+ z + 1) (C2)
2
(b) z
5
1 = 0
z = cos 0 + i sin 0 (accept z = 1).
cos

,
_

t t
,
_

t
,
_

t +
,
_

t
5
4
sin i
5
4
cos ,
5
2
sin i
5
2
(C3)

,
_

t t
5
4
sin i
5
4
cos ,
5
2
sin i
3
2
cos Accept
3

(c)
1
5
2
cos 2
5
2
sin i
5
2
cos
5
2
sin i
5
2
cos
2
+
,
_

,
_

+
,
_

z z z z
(M1)(C1)
1
5
4
cos 2
5
4
sin i
5
4
cos
5
4
sin i
5
4
cos
2
+
,
_

,
_

+
,
_

z z z z
(M1)(C1)
Thus, z
4
+ z
3
+ z
2
+ z + 1 =

,
_

+
1
]
1

,
_

+
1
]
1

1
5
4
cos 2 1
5
2
cos 2
2 2
z z z z
(C1)

OR
z
4
+ z
3
+ z
2
+ z + 1 =

,
_

+
1
]
1

,
_

+
1
]
1

1
5

cos 2 1
5
2
cos 2
2 2
z z z z
(C1)
OR
z
4
+ z
3
+ z
2
+ z + 1 = (z
2
0.618z + 1)(z
2
+ 1.618z + 1) (C1)
5
[10]
1
3. z =
4
3 2
24

isin
24

cos
3

isin
3

cos
4

isin
4

cos

,
_

,
_

,
_

## (a) (i) |z|= 1 (A1)

(ii) z =
4
3
2
24

isin
24

cos
3

isin
3

cos
4

isin
4

cos

,
_

,
_

,
_

,
_

,
_

,
_

,
_

(M1)
arg z = 2

,
_

,
_

,
_

24

4
3

3
4

(M1)
=
6

2

+ +
=
3
2
(A1)
OR
arg z =
3
2
4

(b) z
3
=
3
3
2
sin i
3
2
cos 1
1
]
1

,
_

+
(M1)
= cos 2 + i sin 2 (M1)
= l + 0i
= 1 (AG) 2
2
(c) (1 + 2z) (2 + z
2
) = 2 + z
2
+ 4z + 2z
3

= 2 + z
2
+ 4z + 2 (since z
3
= 1) (Ml)
= 4 + z
2
+ 4z
OR
= 4 + z
2
+ 4z
4 + cos

,
_

+
,
_

+
,
_

+
,
_

3
2
sin i 4
3
2
cos 4
3
4
sin i
3
4
(M1)(A1)
2
i 3 3
2
3
+
(A1)(A1)
= 1 + z + z
2
+ 3 + 3z
= 3 + 3z (since 1 + z + z
2
= 0) (M1)
= 3 + 3

,
_

+
3
2
sin i
3
2
cos
(M1)
= 3 + 3

,
_

+
2
3 i
2
1

(A1)
=
i
2
3 3
2
3
+
(A1) 5
[11]

4. (a) (cos + i sin )
n
= cos (n) + i sin (n), n
+
Let n = 1 cos + i sin = cos which is true. (A1)
Assume true for n = k (cos + i sin )
k
= cos (k ) + i sin (k) (M1)
Now show n = k true implies n = k + 1 also true. (M1)
(cos + i sin )
k+1
= (cos + i sin )
k
(cos + i sin ) (M1)
= (cos (k ) + i sin (k )(cos + i sin )
= cos (k ) cos sin (k )sin +i(sin (k ) cos + cos (k ) sin) (A1)
= cos (k + ) + i sin (k + )
= cos (k + 1) + 1 sin (k + 1) n = k + 1 is true. (A1)
Therefore by mathematical induction statement is true for n 1. (R1)
7

(b) (i) z
1
= 2

,
_

,
_

+
,
_

5
2
isin
5
2
cos

5
1
z
= 2
5
(cos 2 + 1 sin 2 ) (M1)
= 32
Therefore z
1
is a root of z
5
32 = 0 (AG)
3
(ii)

,
_

+
5
4
isin
5
4
cos 4
2
1
z

,
_

+
5
6
isin
5
6
cos 8
2
1
z

,
_

+
5
8
isin
5
8
cos 16
4
1
z
5
1
z
= 32(cos 2 + i sin 2 )(= 32(cos 0 + i sin 0) = 32) (A2)
Note: Award (A2) for all 4 correct, (A1) for 3 correct, (A0)
otherwise.

(iii)
8
8
6
6
4
4
2
2
2
2
4
4
6
6
8 1 01 21 41 61 82 02 22 42 62 83 03 2
1 0
1 2
1 4
1 6
z
z
z
z
z
R e
I m
1
2
1
5
1
4
1
3
1
(A1)(A3)
Note: Award (A1) for graph of reasonable size, scale, axes
marked, (A3) for all 5 points correctly plotted, (A2) for 4 points
correctly plotted. (A1) for 3 points correctly plotted.

(iv) Composite transformation is a combination of (in any order)
an enlargement scale factor 2, centre (0, 0); (A1)
a rotation (anti-clockwise) of
5
2
(72), centre (0, 0)

,
_

) 288 (
5
8
clockwise or
(A1)
9
Note: Do not penalize if centre of enlargement or rotation not
given.
[16]
4
5.

,
_

+
2
sin i
2
cos 8 i 8
3 3

z z
(A1)

) sin i (cos + r z
where
) 2 (
2
3 and 8
3

n r +
(A1)(A1)

,
_

+
6
sin i
6
cos 2
1

z
(A1)

,
_

+
6
5
sin i
6
5
cos 2
2

z
(A1)

,
_

+
,
_

+
2
sin i
2
cos 2 or
2
3
sin i
2
3
cos 2
3 3

z z
(A1)
(C6)
[6]

6. (a) z
n
= cos n + i sin n
n
z
1
= cos (n ) + i sin (n ) (M1)
= cos n i sin (n ) (A1)
Therefore
n z
n
n
cos 2
2
1
+
(AG)
2

(b)
4 3 2
2 3 4
4
1 1
4
1
) ( 6
1
4
1
z z
z
z
z
z
z z
z
z +
,
_

+
,
_

+
,
_

+
,
_

+
(M1)
6
1
4
1
2
2
4
4
+
,
_

+ + +
z
z
z
z
(M1)
(2 cos )
4
= 2 cos 4 + 8 cos 2 + 6 (A1)
) 6 2 cos 8 4 cos 2 (
16
1
cos
4
+ +
(A1)
) 3 2 cos 4 4 (cos
8
1
+ +
(AG) 4
5
(c) (i)

+ +
a a
0 0
4
d ) 3 2 cos 4 4 (cos
8
1
d cos
(M1)
a
0
3 2 sin 2 4 sin
4
1
8
1
1
]
1

+ +
(A1)

,
_

+ + a a a a g 3 2 sin 2 4 sin
4
1
8
1
) (
(A1)

(ii)

,
_

+ + a a a 3 2 sin 2 4 sin
4
1
8
1
1
a = 2.96 (A1)
Since cos
4
0 then g (a) is an increasing function so
there is only one root. (R1)
5
[11]
6
7. METHOD 1
3
, 2

r
(A1)(A1)
( )
3
3
3
3
sin i
3
cos 2 3 i 1

,
_

,
_

+
,
_

M1
( ) sin i cos
8
1
+
(M1)
8
1

A1
METHOD 2
(1
i 3
)(1
i 3
) = 1 2
i 3
3 (= 2 2
i 3
) (M1)A1
(2 2
i 3
)(1
i 3
) = 8 (M1)(A1)
( )
8
1
i 3 1
1
3

A1
METHOD 3
Attempt at Binomial expansion M1
(1
i 3
)
3
= 1 + 3(
i 3
) + 3 (
i 3
)
2
+ (
i 3
)
3
(A1)
= 1 3
i 3
9 + 3
i 3
(A1)
= 8 A1
( )
8
1
i 3 1
1
3

M1
[5]

8. (a) EITHER
5
5
5
2
sin i
5
2
cos
,
_

+

w
(M1)
= cos 2 + i sin 2 A1
= 1 A1
Hence w is a root of z
5
1 = 0 AG
7
OR
Solving z
5
= 1 (M1)
z = cos
. 4 , 3 , 2 , 1 , 0 ,
5
2
sin i
5
2
+ n n n

A1
n = 1 gives cos
5
2
sin i
5
2
+
which is w A1

(b) (w 1)(1 + w + w
2
+ w
3
+ w
4
) = w + w
2
+ w
3
+ w
4
+ w
5
1
w w
2
w
3
w
4
M1
= w
5
1 A1
Since w
5
1 = 0 and w

1, w
4
+ w
3
+ w
2
+ w + 1 = 0. R1
8
(c) 1 + w + w
2
+ w
3
+ w
4
=
+
,
_

+ + + +
2
5
2
sin i
5
2
cos
5
2
sin i
5
2
cos 1

4 3
5
2
sin i
5
2
cos
5
2
sin i
5
2
cos
,
_

+ +
,
_

+

(M1)
+ + + + +
5
4
sin i
5
4
cos
5
2
sin i
5
2
cos 1

5
8
sin i
5
8
cos
5
6
sin i
5
6
cos

+ + +
M1
+ + + + +
5
4
sin i
5
4
cos
5
2
sin i
5
2
cos 1

5
2
sin i
5
2
cos
5
4
sin i
5
4
cos

+
M1A1A1
Notes: Award M1 for attempting to replace
6
and 8 by 4 and 2 .
Award A1 for correct cosine terms
and
A1 for correct sine terms.
0
5
2
cos 2
5
4
cos 2 1 + +

A1
Note: Correct methods involving equating
real
parts, use of conjugates or
reciprocals are
also accepted.
2
1
5
4
cos
5
2
cos +

AG
Note: Use of cis notation is acceptable
throughout
this question.
[12]
9
9. (a)
2 i 1 or 2 3 i 1 +
(A1)
arg
( )
3
3 i 1

+
or arg (1 i) =
4

,
_

4
7
accept

(A1)
m
z 2
1

A1
n
z 2
2

A1
arg (z
1
) = m arctan
3
3

m
A1
arg (z
2
) = n arctan (1) =
4

n

,
_

4
7
accept

n
A1
N2

(b)
m n
n
m
2 2 2
(M1)A1
integer an is where , 2
4 3
k k n m

+

M1A1
k n m

2
4 3
+
k m m

2
4
2
3
+
(M1)
k m 2
6
5

k m
5
12

A1
The smallest value of k such that m is an integer is 5, hence
m = 12 A1
n = 24. A1 N2
[14]
10